Enhancing irrigated forage crop production through water and nutrient management in the Ethiopian sub-humid highlands - Abidela, Misbah; Haileslassie, Amare; Bezabih, Melkamu; Assefa, T.; Tessema, Fikadu; Adie, Aberra; Kassie, A.; Jones, Christopher S.; Tilahun, Seifu A. (Frontiers Media, 2024)
Introduction: The increasing pressure on land and water resources, fueled by high population growth and climate change, has profound implications for crop yield and quality. While studies thrive for various crops, a notable research gap exists in understanding the responses of forage crops to irrigation and nutrient management in developing countries. This study aims to address this gap by assessing the impact of irrigation and fertilizer application on forage production in the Ethiopian sub-humid highlands.